New Technique to Encryption and Embed Secret Messages Based on Lightness Layer in Color Model and Image Processing Methods - Nayif Mohammed Hammash; Mohammed Waleed Nofan; Ahmed S. Abdullah (Genius Journals, 2022)
One of the most important topics seeks to develop algorithms previously or through the discovery of other algorithms that help maintain secret data that has great importance and which the sender seeks not to be discovered by any person who is not authorized to access it, in this article is provided Proposed by digital photo processing methods in increasing the efficiency of this proposed method and at the same time the nature of a non-known chromatic system for many people trying to identify hidden data through the knowledge of the most commonly used ecosystems such as green, red and blue chromatography system, the algorithm have been implemented Suggested on many different images with different nature as well as different texts are included after converting these ports to a binary representation, after applying this algorithm has relied on many criteria that can measure the efficiency of the algorithm were PSN, MSE, and the results of the algorithm force Used.
Keywords: Information; Image processing; security; color space